Oxidative metabolism of koumine is mainly catalyzed by microsomal CYP3A4/3A5. (3rd July 2017) - Hu, Yanxian; Wang, Zhaoyu; Huang, Xin; Xia, Bijun; Tang, Lan; Zheng, Zhijie; Ye, Ling
Abstract: 1.  Gelsemium elegans Benth (Loganiaceae) is a toxic plant that can be used for committing suicide besides alleviating pains. Its anti-inflammatory and analgesic effect mainly come from its active ingredient, namely koumine. Koumine, an indole alkaloid, possesses widely pharmacological effects especially inhibition of neuropathic pain. 2. This study aimed to investigate the metabolic profile of koumine using human liver microsomes (HLMs), selective chemical inhibitors and recombinant human CYP isoforms. Ultra-performance liquid chromatography-high-resolution mass spectrometry (UPLC-HRMS) was used to detect and identify metabolites. 3. Four major metabolites of koumine were found after incubation with HLMs or individual CYP isoforms. The metabolic pathways of koumine included demethylation, dehydrogenation, oxidation and demethyl-dehydrogenation. Chemical inhibition study showed that the inhibitor of CYP3A4/3A5 significantly decreased (93%) the formation of koumine metabolites. Further, CYP3A4/3A5 was shown as the most efficient isoform in biotransformation of koumine, among a series of CYP isoforms tested. 4. In conclusion, koumine was metabolized into four oxidative metabolites in HLMs. And CYP3A4/3A5 was probably the main contributor to the hepatic oxidative metabolism of koumine.